The impacts of shock events on airport management and operations: a systematic literature review - Gu, Yue; Wiedemann, Mirjam; Freestone, Robert; Rothe, Henrik; Stevens, Nicholas (Elsevier, 2024)
Unpredictable shock events have disruptive and long-lasting impacts on the aviation industry. However, the scale and type of impact of different shock events on airport operations and planning have been unevenly surveyed. A better understanding can help airports to improve their risk mitigation and develop more resilient operations and management. Through a systematic literature review of peer-reviewed research, we summarise shock events into four categories based on the cause of the shock: economic recessions, infectious disease pandemics, terrorist attacks, and natural disasters. The major impacts are identified as a reduction in air travel demand, interruptions in operations, modified operating procedures, and changes in facilities and infrastructure. We further bring these together into a conceptual typology of event-impact interactions. This longitudinal overview may assist airport managers in better understanding the impacts of shock events and taking further steps in developing more resilient airport infrastructure and associated business models.
Keywords: 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 3304 Urban and regional planning; Shock events; Airport planning; Resilience; Airport strategy; Airport business model